Cell and Molecular Biology of Breast Cancer - Schatten, Heide (Humana Press : Imprint: Humana, 2013)
Highlighting recent advances in our understanding of breast cancer, this book is intended for a wide audience as a reference book. Included are reviews of genetics, epigenetics, various aspects of cell and molecular biology, and several other areas of breast cancer that are aimed at determining new intervention sites for treatments and cures of the disease. The chapters are written by internationally recognized experts and include reviews of key topics in breast cancer research. Each chapter highlights the new aspects of specific research topics, the various impacts of designing new strategies, and identifies new targets for therapeutic intervention. The topics addressed are selected to be of interest to patients, scientists, students, teachers, and to all who are interested in expanding their knowledge of breast cancer imaging, diagnostics, therapeutics, or basic biomedical research on breast cancer.